Impact of e-liquid flavors on e-cigarette vaping behavior. (1st August 2018) - St.Helen, Gideon; Shahid, Marian; Chu, Sherman; Benowitz, Neal L.
Highlights: Vaping topography and patterns of use differ across e-liquids. The relationship between topography and nicotine exposure differs across e-liquids. Puff count and extent of clustered puffing predicts amount of e-liquid consumed. Abstract: Objective: The primary objective of this pilot study was to describe the impact of e-cigarette liquid flavors on experienced e-cigarette users' vaping behavior. Methods: 11 males and 3 females participated in a 3-day inpatient crossover study using e-cigarettes with strawberry, tobacco, and their usual brand e-liquid. Nicotine levels were nominally 18 mg/mL in the strawberry and tobacco e-liquids and ranged between 3–18 mg/mL in the usual brands. On each day, participants had access to the study e-cigarette (KangerTech mini ProTank 3, 1.5 Ohms, 3.7 V) and the assigned e-liquid during a 90-minute videotaped ad libitum session. Results: Average puff duration was significantly longer when using the strawberry e-liquid (3.2 ± 1.3 s, mean ± SD) compared to the tobacco e-liquid (2.8 ± 1.1 s) but the average number of puffs was not significantly different (strawberry, 73 ± 35; tobacco, 69 ± 46). Compared to the strawberry- and tobacco-flavored e-liquids, average puff duration was significantly longer (4.3 ± 1.6 s) and the average number of puffs was significantly higher (106 ± 67 puffs) when participants used their usual brand of e-liquid. Participants generally puffed more frequently in small groups of puffs (1–5 puffs) with the strawberry compared to the tobacco e-liquid and more frequently in larger groups (>10 puffs) with their usual brand. The strength of the relationship between vaping topography and nicotine intake and exposure were not consistent across e-liquids. Conclusion: Vaping behavior changes across e-liquids and influences nicotine intake. Research is needed to understand the mechanisms that underlie these behavioral changes, including e-liquid pH and related sensory effects, subjective liking, and nicotine effects.